Green Tea Extract Solid Dispersion Pellets with Enhanced Permeability for Hyperlipidemia - Vinita Patole; Pranita Gaikwad; Shashikant Kharat; Pranali Jadhav; Sanjeevani Deshkar; Prabhanjan Giram (MDPI AG, 2023)
Green tea extract, rich in polyphenols like catechins, has been reported to have pharmacological benefits in patients with hyperlipidemia. The minimal membrane permeability of green tea limits its use in terms of bioavailability. To improve the permeability of green tea catechins in order to enhance theiranti-hyperlipidemia activity, a surfactant-based polymer was used to formulate a solid dispersion of green tea and convert it into commercially acceptable pellets. Green tea extract solid dispersions (GTE-SDs) were prepared withsolvent evaporation method using Soluplus® as a carrier. The GTE-SDs were evaluated for ex vivo permeation studies and characterized using FTIR, DSC, and XRD for confirming the formation of SD. The GTE-SDs exhibiting enhanced ex vivo permeation of EGCG were converted into a pellet formulation using the extrusion spheronization technique while being optimized using a 32 full factorial design. Soluplus® exhibited a four-fold improvement in the ex vivo permeation of EGCG from GTE-SD pellets (33.27%) as compared to GTE (10.43%) (p-value < 0.0001). In male Wistar rats, optimized GTE-SD pellets reduced the lipid blood profiles as compared to GTE (p-value < 0.0001). Thus, GTE-SD pellets can serve as an effective drug delivery platform for hyperlipidemia.